2007
DOI: 10.1590/s0102-09352007000400037
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do resfriamento sobre a textura post-mortem da carne do peixe matrinxã Brycon cephalus

Abstract: Efeito do resfriamento sobre a textura post-mortem da carne do peixe matrinxã Brycon cephalus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In addition, microorganisms can synthesize new fatty acids, elongating and desaturating the carbon chain (Ekasari et al, 2010). The significant presence of PUFA n-3 and n-6 in the biofloc, such as α-linolenic (C 18:3 n-3), can be elongated and desaturated to produce EPA and DHA, however, the process occurs in a low percentage (Suárez-Mahecha et al, 2002). In the present study, this fatty acid was not found with significant amounts in fish reared in BFT.…”
Section: Lipid Profilementioning
confidence: 99%
“…In addition, microorganisms can synthesize new fatty acids, elongating and desaturating the carbon chain (Ekasari et al, 2010). The significant presence of PUFA n-3 and n-6 in the biofloc, such as α-linolenic (C 18:3 n-3), can be elongated and desaturated to produce EPA and DHA, however, the process occurs in a low percentage (Suárez-Mahecha et al, 2002). In the present study, this fatty acid was not found with significant amounts in fish reared in BFT.…”
Section: Lipid Profilementioning
confidence: 99%
“…Species of Brycon are used in commercial production and fi sh farming in Brazil (Wasko, 2005;Ninhaus-Silveira et al, 2006). The Bryconids have several advantages for fi sh farming, including their omnivorous feeding habits and their adaptation to low levels of oxygen (Suarez-Mahecha, 2002). There is a growing search for Brycon spp.…”
Section: Diversity Of Fi Sh and Species Threatened With Extinctionmentioning
confidence: 99%
“…Among the main methods of evaluating freshness, sensorial, physicochemical, and microbiological methods stand out (de Paiva Soares & Gonçalves, 2012). Another characteristic of fundamental importance is firmness, a significant factor for evaluating fish meat quality and is directly related to its freshness (Suárez-Mahecha et al, 2007). Amaral and Freitas (2013) also state that firmness plays a fundamental role in the consumers' acceptance of meat protein.…”
mentioning
confidence: 99%